Load forecasting analysis for estimating transformer capacity of Karangkates Substations using Holt-Winters method in Python - Rahmawati, Yuni; Kaki, Gregorius Paulus Mario Laka; Aripriharta, Aripriharta; Sujito, Sujito; Afandi, Arif Nur; Wibawa, Aji Prasetya; Purwatiningsih, Ayu; Bagaskoro, Muhammad Cahyo; Omar, Saodah; Rosmin, Norzanah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
In the six years from 2010 to 2015, the peak load in the East Java region increased by an average of 284MW per year. Karangkates Substation is part of an interconnected electrical system that supplies Java Island. To ensure a high level of reliability in its service, it is necessary to prepare for load growth to make sure that it does not exceed its ideal conditions, therefore special analysis of transformer capacity is needed. Using the Holt-Winters (HW) method as a reference for processing the data can be used as a reference in planning and anticipating the growing electricity demand. The results of this study are with the accuracy of the HW method with mean absolute percentage error (MAPE) = 2.645%, while the accuracy of the fuzzy time series (FTS) method = 6.399%. A forecast result done with HW methods shows the transformer at the substation Karangkates reached its normal working capacity in March 2018 at 99.583% of installed capacity and exceeded the maximum capacity in April 2018 at 101.493% of installed capacity.